KAMEDIN: A Telemedicine System for Computer Supported Cooperative Work and Remote Image Analysis in Radiology - Heinz Handels; Busch, C; Encarnação, J; Hahn, C; Kühn, V; Miehe, J; Siegfried J. Pöppl; Rinast, E; Roßmanith, Christina; Seibert, F; Will, A (Computer methods and programs in biomedicine, 1997)
The software system KAMEDIN (Kooperatives Arbeiten und MEdizinische Diagnostik auf Innovativen Netzen) is a multimedia telemedicine system for exchange, cooperative diagnostics, and remote analysis of digital medical image data. It provides components for visualisation, processing, and synchronised audio-visual discussion of medical images. Techniques of computer supported cooperative work (CSCW) synchronise user interactions during a teleconference. Visibility of both local and remote cursor on the conference workstations facilitates telepointing and reinforces the conference partner's telepresence. Audio communication during teleconferences is supported by an integrated audio component. Furthermore, brain tissue segmentation with artificial neural networks can be performed on an external supercomputer as a remote image analysis procedure. KAMEDIN is designed as a low cost CSCW tool for ISDN based telecommunication. However it can be used on any TCP/IP supporting network. In a field test, KAMEDIN was installed in 15 clinics and medical departments to validate the systems' usability. The telemedicine system KAMEDIN has been developed, tested, and evaluated within a research project sponsored by German Telekom.
Keywords: Humans; Radiographic Image Enhancement; Software; Teleradiology